(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the capabilities of the ChemCollective virtual laboratory in teaching one of the main branches of analytical chemistry titrimetric analysis (acid-base and redox titrations). The platform helps reinforce students’ theoretical knowledge, develop practical skills, and effectively conduct laboratory sessions even in remote learning environments.